Novel approach for preparing nontoxic stealth microspheres for drug delivery - Angra, Pawan Kumar; Rizvi, Syed Asad Ali; Oettinger, Carl William; D’Souza, Martin Joaquim (European Journal of Chemistry, 2011)
<!--[if gte mso 9]> Normal.dotm 0 0 1 124 709 Uni 5 1 870 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> Polyethylene glycol 2000 (PEG) entrapped, bovine serum albumin (BSA) microspheres were prepared and optimized. These microspheres were then analyzed to understand the stealth effect to the microspheres imparted by incorporated polyethylene glycol (PEG). Microsphere preparations (formulations) were studied for particle size, zeta potential, free BSA content, and in-vitro uptake by human micro-vascular endothelial cells (HMECs). The results demonstrate, a formulation containing 37.5 % PEG (w/w) exhibits an acceptable particle size of <5 µm, good suspendibility with zeta potential of -35 mV, and confers some degree of stealth property to the microspheres. These non-toxic, biodegradable and long circulating microspheres have the potential to be used for extended intravenous (IV) drug delivery. Statistical analysis done by ANOVA and results with p<0.05 were considered significant.